Perception and Adaptation of Coastal Community Toward Climate Change at Sarawet Village of North Minahasa Regency - Isdomo Yuliantoro; Nurlita Indah Wahyuni (Jurnal Wasian, 2019)
Climate change is difficult phenomenon to be understood by ordinary community. Whereas perception and knowledge of climate change will influence mitigation and adaptation, which can decrease risks of climate change impact. The research aims to find out community’s perception about climate change and adaptation efforts which have been done by communities of Sarawet Village at North Minahasa Regency. Perception and adaptation data were obtained through interview and focus group discussion. The result shows that 96.67 % of community has experienced the symptoms and impacts of climate change, which perceived as extreme season or the shift of rain and drought season. The most perceived climate change impacts are crop failure, less income from agriculture and drought. This perception indicates a lack of environmental and forestry information. The adaptation efforts that have been done by the community include change plant species that need lack water as well as fulfill needs of clean water from the central well and utilize springs from upstream. Based on SWOT analysis An appropriate strategy to encourage adaptation in Sarawet village is done through increasing the adaptive capacity of the community Keywords: perception, climate change, SWOT, adaptive capacity